Looking for Wi-Fi: youth homelessness and mobile connectivity in the city. Issue 7 (19th May 2021) - Humphry, Justine
ABSTRACT: Studies of digital disparities have focused on socio-spatial differences across neighbourhoods, regions and other kinds of places, but the same place can produce different experiences of connectivity, a phenomenon labelled 'variable geometries of connection' by Crang, Crosbie and Graham (2006: 2551) [2006. Crang, M., Crosbie, T., & Graham, S. Variable geometries of connection: Urban digital divides and the uses of information technology. Urban Studies, 43 (13), 2551–2570]. In this paper, I draw on research on the role of mobile phones and the internet for people experiencing homelessess in Australia to suggest that dependence on smartphones for access to information and communication when homeless, in combination with the design and regulation of urban spaces, structures the mobilities of homeless young people, resulting in distinctive connectivity needs and barriers. Homeless young people overcome many of their immediate difficulties of digital access through practices of 'survival infrastructuring', a term I propose to describe the practices of marginalised actors to make their media work in the face of uneven, precarious and costly connectivity. Highlighting these connectivity experiences and practices may help efforts to take action on digital exclusion and assist homeless young people by taking into account differential access needs within specific spatial and social contexts. I make this argument drawing on findings from two studies carried out between 2014 and 2016 on the access and use of the internet and mobile phones among homeless Australians.